North Korea's nuclear-armed missiles : options for the US and its allies in the Asia-Pacific - Paul, Michael; Suh, Elisabeth (2017)
Zusammenfassung: During his presidential campaign, Donald Trump unsettled the governments of Japan and South Korea by suggesting they should develop their own nuclear weapons to defend against the missile threat from North Korea. When Pyongyang announced the launch of four missiles towards the island of Guam, a US territory in the West Pacific, President Trump demanded North Korea stop issuing threats against the US or “they will be met with fire and fury”. Instead of bellicose rhetoric, however, diplomacy is needed to bring about de-escalation and dialogue with North Korean leader Kim Jong-un. Pyongyang has made significant advancements in its nuclear and missile weapons programmes. Washington is now faced with the quandary of how to react to the growing threat both to its allies and to its own territory. None of the policy options available to the US and its allies in the Asia-Pacific region seem promising and can, at best, only be successful in the long term